Migraine in children under 6 years of age: A long-term follow-up study. (July 2020) - Marchese, Francesca; Rocchitelli, Luciana; Messina, Luca Maria; Nardello, Rosaria; Mangano, Giuseppe Donato; Vanadia, Francesca; Mangano, Salvatore; Brighina, Filippo; Raieli, Vincenzo
Abstract: Background: Early starting of migraine seems predictive for less favorable outcome in later ages, however follow-up investigations are very few and all with short-term prospective period. We report here the longest follow-up study in a population of children presenting with migraine under the age of 6. Methods: We followed-up 74 children under 6 years of age, referred for headache to our department between 1997 and 2003. The study was carried out between October 2016 and March 2018. Headache diagnoses were made according to the IHS criteria. Results: 23/74 patients, 31% of the original cohort, were found at follow-up in a period ranging between 15 to 21 years after the first visit. Seven of them were headache free. The remaining 16 patients had migraine. In the migraine group, the localization of pain changed in 75% of the subjects, 11/16 (68.7%) had allodynia and 9/16 (56.25%) had cranial autonomic symptoms. Conclusions: Our results suggest that the onset of migraine at very young age represents unfavorable prognostic factor for persistence of the disease at later ages. Some clinical features may change during clinical course, and the active persistence of the disorder may lead to an increase in allodynia. Highlights: The prevalence of autonomic cranial symptoms and familiarity suggest the persistence of migraine in adulthood. The migraine persistence facilitates the sensitization of neural centers associated to pain leading to increased allodynia. Several clinical feature of migraine syndrome may change during the follow-up. The prevalence of autonomic cranial symptoms and the familiarity of migraine suggest the persistence of migraine in adulthood, while the active persistence of the disorder may facilitate the strengthening of the sensitizing neural centers associated with pain leading to increased allodynia.